2009
DOI: 10.1016/j.jadohealth.2008.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Subjective Social Status on the Relationship Between Positive Outcome Expectations and Experimentation with Cigarettes

Abstract: Purpose-In Texas, Mexican American (MA) adolescents, and in particular boys, are at increased risk of experimenting with cigarettes compared to their black or white counterparts. Positive outcome expectations (POE), the functional social significance ascribed to cigarettes, and subjective social status (SSS), the adolescents' subjective views of where they lie in the school-based social hierarchy, are independent predictors of smoking. The goal of this study was to test the hypothesis that SSS moderates the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 32 publications
5
34
0
2
Order By: Relevance
“…It is important to note that these findings held even when we controlled for several risk factors associated with cigarette experimentation, including positive outcome expectations (Dalton et al, 1999; Spelman et al, 2009), subjective social status (Finkelstein, Kubzansky, & Goodman, 2006; Wilkinson, Shete et al, 2009), peer influence (U.S. DHHS, 2012; Wilkinson, Spitz et al, 2009) and family influence (Chalela, Velez, & Ramirez, 2007; Spelman et al, 2009), and sensation seeking tendencies (Adachi-Mejia, Carlos, Berke, Tanski, & Sargent, 2012; Wilkinson et al, 2012).…”
Section: Discussionmentioning
confidence: 87%
“…It is important to note that these findings held even when we controlled for several risk factors associated with cigarette experimentation, including positive outcome expectations (Dalton et al, 1999; Spelman et al, 2009), subjective social status (Finkelstein, Kubzansky, & Goodman, 2006; Wilkinson, Shete et al, 2009), peer influence (U.S. DHHS, 2012; Wilkinson, Spitz et al, 2009) and family influence (Chalela, Velez, & Ramirez, 2007; Spelman et al, 2009), and sensation seeking tendencies (Adachi-Mejia, Carlos, Berke, Tanski, & Sargent, 2012; Wilkinson et al, 2012).…”
Section: Discussionmentioning
confidence: 87%
“…49 If these adolescents believe that they are in worse standing than others, then they might be more inclined to smoke, especially if they think it will raise their social status to their peers’ level. 17 We also found that adolescents who think that they are going to smoke in the future were more likely to escalate. This finding really exemplifies the strength of the favorable attitudes toward smoking in affecting actual smoking behavior.…”
Section: Discussionmentioning
confidence: 58%
“…1316 Our group has focused on identifying risk factors for smoking experimentation and initiation among the Mexican heritage population in the United States. We have found that that low to moderate subjective social status combined with holding positive outcome expectations for smoking resulted in higher risk of adolescent experimentation 17 and that family conflict is associated with an increased risk for adolescent smoking while family cohesion decreases the risk. 18 Increased levels of anxiety, 19 age, sex, cognitive susceptibility, peer influence, and household smoking behavior were all associated with smoking experimentation as well.…”
Section: Introductionmentioning
confidence: 81%
“…Positive outcome expectations(14, 15, 20, 22, 23), household smoking(1417), neighborhood characteristics(52), anxiety and depression(25, 53), and school suspensions(54)have also been shown to be associated with smoking experimentation in several studies. Our study also found that family cohesion, co-worker smoking status, and acculturation were associated with smoking experimentation.…”
Section: Discussionmentioning
confidence: 99%